Teleskopische Generationsnarrative. Elisabeth Reicharts «Die Voest-Kinder» und Melitta Brezniks «Der Sommer hat lange auf sich warten lassen» (Studia austriaca, 2014)
This is a comparative reading of Die Voest-Kinder (2011) by E. Reichart and Der Sommer hat lange auf sich warten lassen (2013) by M. Breznik. Both novels participate in a recent trend in Austrian and German contemporary literature; they explore how history, primarily family history, is passed on in a trans-generational perspective: as transmitted silence. It is here that we find the origin of traumas in life and in these two novels, not only for those directly affected by the traumatic events, but also for the following generations. Traumatic experiences are transmitted by what S. Weigel, based on the psychoanalyst H. Faimberg, describes as «telescoping».